Don't forget me, little Bessie [compact disc, unabridged] - Burke, James Lee, 1936- (Burke, James Lee, 1936- Holland family saga., 2025)
At the beginning of the twentieth century, as America grapples with forces of human and natural violence more powerful than humanity has ever seen, Bessie Holland yearns for the love that she has never known. She finds a soulmate and mentor in a brilliant but tormented suffragette English teacher, who inspires Bessie to fight the forces of evil that permeate her world. Watching the vast Texas countryside being destroyed by an oil company and a menacing figure with a violent past, Bessie is prepared to defend her home and her family. But when she accidentally kills an unarmed man to defend her father Hackberry, she must flee to New York. There, her older brother introduces her to boys who will grow into gangsters, but as children admire and respect Bessie's spirit and fortitude as she is cast into a gangland that yearns for justice and mercy.